Management strategies and clinical outcomes of acute myocardial infarction in leukaemia patients: Nationwide insights from United States hospitalisations. Issue 5 (20th January 2020) - Mohamed, Mohamed O.; Lopez‐Mattei, Juan C.; Parwani, Purvi; Iliescu, Cezar A.; Bharadwaj, Aditya; Kim, Peter Y.; Palaskas, Nicolas L.; Rashid, Muhammad; Potts, Jessica; Kwok, Chun Shing; Gulati, Martha; Al Zubaidi, Abdul Majeed Brek; et al.
Summary: Background: Patients with leukaemia are at increased risk of cardiovascular events. There are limited outcomes data for patients with a history of leukaemia who present with an acute myocardial infarction (AMI). Methods: We queried the Nationwide Inpatient Sample (2004‐2014) for patients with a primary discharge diagnosis of AMI, and a concomitant diagnosis of leukaemia, and further stratified according to the subtype of leukaemia. Multivariable logistic regression was conducted to identify the association between leukaemia and major acute cardiovascular and cerebrovascular events (MACCE; composite of mortality, stroke and cardiac complications) and bleeding. Results: Out of 6 750 878 AMI admissions, a total of 21 694 patients had a leukaemia diagnosis. The leukaemia group experienced higher rates of MACCE (11.8% vs 7.8%), mortality (10.3% vs 5.8%) and bleeding (5.6% vs 5.3%). Following adjustments, leukaemia was independently associated with increased odds of MACCE (OR 1.26 [1.20, 1.31]) and mortality (OR 1.43 [1.37, 1.50]) without an increased risk of bleeding (OR 0.86 [0.81, 0.92]). Acute myeloid leukaemia (AML) was associated with approximately threefold risk of MACCE (OR 2.81 [2.51, 3.13]) and a fourfold risk of mortality (OR 3.75 [3.34, 4.22]). Patients with leukaemia were less likely to undergo coronary angiography (CA) (48.5% vs 64.5%) and percutaneous coronary intervention (PCI) (28.2% vs 42.9%) compared with those without leukaemia. Conclusion: Patients with leukaemia, especially those with AML, are associated with poor clinical outcomes after AMI, and are less likely to receive CA and PCI compared with those without leukaemia. A multi‐disciplinary approach between cardiologists and haematology oncologists may improve the outcomes of patients with leukaemia after AMI.